Investigation of the influence of vibration oscillations in the processes of strengthening processing of machine parts - Dudnikov, Anatolii; Dudnik, Vladimir; Kanivets, Oleksander; Bilovod, Oleksandra; Burlaka, Oleksii (Technology audit and production reserves, 2018)
The object of research is the technological process of improving the reliability of the recovery of ploughshare disks of grain seeders by vibration hardening. One of the most problematic places is the lack of knowledge of this process in the restoration of agricultural machinery. For the emergence of a deeper understanding of the process of vibration hardening of the material of parts, it is necessary to conduct experimental studies on the effect of processing parameters on the hardening degree. In the course of research, the process of vibration hardening of the weld surface is carried out on a vibration installation made by the authors of this study. To select processing parameters and determine their optimal values, microstructural studies of the disk material are carried out. The main parameters of hardening are revealed and substantiated: amplitude and frequency of oscillations of the processing tool, hardening time, and their values are determined: A=0.5 mm; n=1400 min-1; t=20 s. As a result of the research, it is established that during vibration hardening, the structure of the material is more fine-grained. The increase in microhardness on the surface of the deposited layer can be explained by the greater fragmentation of grains and an increase in their number. This, in turn, causes the activation of dislocations in all grains adjacent to the surface. During vibration deformation, the length of the grain boundaries increases and thereby more dislocation slip zones are formed. This can explain the hardening mechanism. The evaluation of the operational reliability of the disks on the following indicators: the performance per season and the coefficient of technical use. For seeders with discs restored by welding segments with sormite surfacing and vibration strengthening, the coefficient of technical use is 1.053 times higher than for seeders with new discs. Thanks to the use of the developed restoration technology, it is possible to reduce the blade blunting speed by 1.49–1.70 times. This provides an increase in the operation time. Compared with similar known technologies, the developed technology of vibration hardening of blades provides the greatest wear resistance and an increase of 1.34 times the operating time compared to new discs.